Makna Kehadiran Dalam Kancah Revolusi Industri 4.0 - Martinus Irwan Yulius (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2020)
The wave of the Industrial Revolution 4.0 has brought enormous changes in all dimensions of life without exception including the church apostolic work, specifically pastoral care. All changes and developments always bring up new challenges that must be responded to correctly and wisely. This large technological development has a major impact on the sense of connectivity in relations between people; on the contrary, this age reduces the meaning of personal presence because one does not need to be physically present to establish relationships with others. It is precisely in this situation humans lose the deepest meaning of a presence; this matter will be discussed more deeply in the context of Pastoral Care that truly prioritize a personal presence. In addition, the next challenge which is the product of developments that will be initiated in this reflection is empathy which actually does not directly refer to presence but refers to a way of life that must be built in growing relations between people.